Drug-eluting stent thrombosis after 2029 days of placement: longest ever reported interval between drug-eluting stent placement and very late thrombosis. (November 2011) - Akhtar, Muhammed; Waked, Alain; Bhat, Hilal; Khalid, Mariam; Teli, Sumaya; Saiful, Faisal B; Lafferty, James; Bhat, Tariq
In this era of very wide-spread use of percutaneous coronary intervention for the management of coronary artery disease, the appropriate duration of antiplatelet therapy after drug-eluting stent implantation still remains a subject of debate. Current recommendations from the American College of Cardiology/American Heart Association (2007) is to continue treatment with aspirin and clopidogrel for 1 year and then continue with aspirin only. However, cases of very late stent thrombosis (more than 12 months postimplantation) are being increasingly reported in literature. In this article we report a case of thrombosis as a result of drug-eluting stent placement after almost 67 months (2029 days), which to our knowledge, is the longest reported duration between the implantation of drug-eluting stent and occurrence of vascular event associated with very late stent thrombosis.